Impact of innovation platforms and information sharing on nurturing of smaller innovation platforms: A case study of Tanzania Dairy Development Forum - Kago, K.M. (Egerton University, 2019)
Information sharing on production, marketing, processing, and consumption among otherindustry attributes is a key determinant on the effectiveness and efficiency of the dairy industry.However, actors in the dairy value chain often lack awareness of where and how to accessinformation or are uncertain concerning the quality and reliability of the information shared withthem. However, innovation platforms bringing together dairy industry stakeholders harbour thepotential to improve accountability and quality of information, to benefit all actors in the dairyvalue chain. Accordingly, several innovation platforms have been established at the village anddistrict levels in Tanzania to address these challenges. Most importantly, the Tanzania DairyDevelopment Forum that was established in 2013 has a mandate to enhance information andknowledge sharing by convening annually to aggregate, synthesize, and disseminate informationrelevant to the dairy industry in Tanzania. In addition, it is also entrusted with the role ofnurturing smaller innovation platforms at the milk-shed level and facilitates evidence-basedinformation sharing to attract more investments from both private and public sectors into thedairy industry. This is expected to have a major impact on market access by smallholder farmersin Tanzania and improve the quality of milk and milk products through joint standards. Theconceptual framework of this study entails focusing on the structure, conduct, and performanceof the Tanzania Dairy Development Forum. Both qualitative and quantitative data will becollected through focus group discussions, key informant interviews, and individualquestionnaires of Tanzania Dairy Development Forum members and non-members. Thereafter,descriptive and inferential statistics will be used to analyse the data with specific focus onANOVA tests, Chi square and Factor Analysis. A mixed methods linear regression model willalso be used. The findings from this study will be useful in characterizing information sharingtrends in the Tanzania dairy industry, and in refining and testing a conceptual framework byILRI for the monitoring and evaluating the impact of innovation platforms